Pertanggungjawaban Para Pihak terhadap Protokol Notaris sebagai Arsip Negara - Listyarini, Dyah (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2019)
Abstract: The problem that often arises in connection with the Notary Protocol is when a Notary dies or retires. This paper intends to study and examine the legal rules related to the transition process of the Notary Protocol as State Archives from the heirs of the Notary who passed away to the Substitute Notary Public and the roles and responsibilities of the Notary Supervisory Council in the process of transitioning the Notary Protocol. Based on the study that has been done, it is found that the process of transferring the Notary Protocol from a Notary who died to a Notary Public is carried out by the Notary's heir who died. In this case, the heirs of a Notary are obliged to submit the Notary Protocol to a Substitute Notary who is appointed by the Notary Supervisory Council. The Notary Supervisory Council plays a role and is responsible for providing guidance and supervision to Notaries and at the same time taking Notary Protocols from the Notary's heirs to be submitted to the Substitute Notary Public.Abstrak: Persoalan yang sering muncul berkaitan dengan Protokol Notaris adalah ketika seorang Notaris meninggal dunia ataupun purna tugas. Tulisan ini hendak mengkaji dan meneliti aturan hukum terkait proses peralihan Protokol Notaris sebagai Arsip Negara dari ahli waris Notaris yang meninggal dunia kepada Notaris Pengganti dan peran serta tanggung jawab Majelis Pengawas Notaris dalam proses peralihan Protokol Notaris tersebut. Berdasarkan kajian yang telah dilakukan diperoleh temuan bahwa proses peralihan Protokol Notaris dari Notaris yang meninggal dunia kepada Notaris Pengganti dilakukan oleh ahli waris Notaris yang meninggal dunia. Dalam hal ini  ahli waris Notaris berkewajiban menyerahkan Protokol Notaris kepada Notaris Pengganti yang ditunjuk oleh Majelis Pengawas Notaris. Adapun Majelis Pengawas Notaris berperan dan bertanggung jawab melakukan pembinaan dan pengawasan kepada Notaris dan sekaligus mengambil Protokol Notaris dari ahli waris Notaris untuk diserahkan kepada Notaris Pengganti.